Picture Guessing Game -Based Learning Module as a means Improving Elementary School Physical Education Learning Outcomes - Yudesta Efaliana; Kuswanto, Cahniyo Wijaya; Putri Zakia; Oktaria Kusumawati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research is based on problems found by researchers, namely the unavailability of teaching materials that are in accordance with the curriculum used and the existing teaching materials do not fully meet the needs of students. This research aims to develop a physical education, sports and health (PJOK) learning module based on a picture guessing game. This research and development uses a model from Robert Maribe Branch. The data collection instrument used a questionnaire given to three experts, namely media experts who scored 76% in the "decent" category, material experts who got a score of 91% in the "very decent" category, and language experts who got a score of 93% in the "very decent" category. and also given to educators who obtained a score of 96% in the "very appropriate" category, as well as small-scale students who obtained a score of 96% and large-scale questionnaire responses 95.6% in the "very appropriate" category. The post test results of small scale students obtained an average score of 90 and the post test results of large scale students obtained an average score of 89. Thus the product developed is feasible and effective in improving student learning outcomes.